The Role of HelloTalk in English Education Students’ Autonomous Speaking - Mareta, Finka; Sakina, Rahma; Ridwan, Revi Nur; Nugraha, Muhammad Anjar (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2025)
Fluent English speaking is essential for English Education students, especially for academic and professional success in global contexts. However, learners often face limited real-life interaction, a lack of feedback, and weak autonomous learning habits. Mobile-Assisted Language Learning (MALL) tools like HelloTalk are increasingly used, yet their specific role in promoting autonomous speaking practice at the university level remains underexplored. This study investigates students’ attitudes toward using HelloTalk to develop autonomous speaking skills and identifies the benefits and challenges they experience. A qualitative descriptive method was used, collecting data through closed-ended questionnaires and semi-structured interviews with English Education students at Ma’soem University who used HelloTalk for at least one month. The findings reveal positive attitudes across cognitive, affective, and behavioral dimensions. Students found HelloTalk motivating, user-friendly, and effective for speaking practice. Key benefits included increased speaking confidence, flexibility, authentic language exposure, and timely feedback from peers and AI. Reported challenges included limited access to premium features, difficulty finding conversation partners, and fluctuating motivation. Overall, HelloTalk supports learner autonomy by providing a flexible, interactive space for language use beyond the classroom. These findings suggest that the integration of MALL tools like HelloTalk into formal curricula can enhance students’ speaking fluency and self-directed learning.